<span>y = slope*x + y-intercept;
</span>We can rewrite our equation in a shorter form : y = mx + b;
y = x + 2 ; m1 = 2 and b1 = 2;
y = -x + 6; m2 = -1 and b2 = 6;
<span>Set the two equations for y equal to each other:
</span>x + 2 = -x + 6 ;
<span>Solve for x. This will be the x-coordinate for the point of intersection:
</span>2x = 4;
x = 2;
<span>Use this x-coordinate and plug it into either of the original equations for the lines and solve for y. This will be the y-coordinate of the point of intersection:
</span>y = 2 + 2 ;
y = 4;
<span>The point of intersection for these two lines is (2 , 4).</span>
Answer:
Step-by-step expla2nation:
1. Plug in numbers
•48=12h
2. Divide 48 by 12
•48/12=12h/12
3. 12/12 cancels out, and 48/12=4
h=4
Answer:
The answer is 20
Step-by-step explanation:
Step-by-step explanation:
<em>Combine like terms</em>
a. 2r + 3 + 4r = (2r + 4r) + 3 = 6r + 3
b. 8 + 3d + d = (3d + d) + 8 = 4d + 8
c. mn + (-3mn) + 6 = (mn - 3mn) + 6 = -2mn + 6
d. 10s + (-10) + (-4s) = (10s - 4s) - 10 = 14s - 10
<em>Terms are called "like terms" if they have the same variable part (the same letters in the same powers). Like terms differ at most coefficient.</em>